Pengaruh Kebijakan Dividen, Likuiditas, Leverage, Profitabilitas, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Monica, Cindy; Setyarini, Yulia (Rifa'Institute, 2022)
The value of the company is an important thing for the company because if the value of the company increase will affect to the company shares price. There are several factors that can affect the size of the value of a company that comes from internal or external companies. This study uses secondary data as many as 30 food and beverage industry companies listed on the Indonesia Stock Exchange. The sample selection in this study used purposive sampling, so as to get a sample of 14 companies. The period used by researchers is 2017-2019. The results of the study using SPSS 22 indicate that the profitability variable has a positive effect on firm value. Meanwhile, the variables of dividend policy, liquidity, leverage, and firm size have no effect on firm value